1998
DOI: 10.1109/91.705512
|View full text |Cite
|
Sign up to set email alerts
|

A survey of recent advances in fuzzy logic in telecommunications networks and new challenges

Abstract: Fuzzy logic has been successfully deployed in many realworld automatic control systems including subway systems, autofocus cameras, washing machines, automobile transmissions, air-conditioners, industrial robots, aerospace, and autonomous robot navigation. In contrast, the use of fuzzy logic in telecommunication systems and networks is recent and limited. Fundamentally, Zadeh's fuzzy set theory provides a robust mathematical framework for dealing with "real-world" imprecision and nonstatistical uncertainty. Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 31 publications
0
43
0
2
Order By: Relevance
“…Fuzzy algorithms [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] are based on different fuzzy parameters to give desirable output in different networks. Authors [15] utilized FL to model the multiobjective routing problem in mobile Ad-hoc networks.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…Fuzzy algorithms [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] are based on different fuzzy parameters to give desirable output in different networks. Authors [15] utilized FL to model the multiobjective routing problem in mobile Ad-hoc networks.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…Uncertainty, imprecision, incompleteness, risk management, partial true and vice versa is an attribute of information in Fuzzy systems [29]. Fuzzy controllers are simple, low cost and can be designed without knowing the mathematical model of the process.…”
Section: Disadvantagementioning
confidence: 99%
“…Besides, detailed discussions and review papers about fuzzy logic applications in telecommunications can be found in refs. 22,23,24 .…”
Section: Related Workmentioning
confidence: 99%